EFEKTIFITAS VARIASI PENAMBAHAN KOTORAN SAPI, DEDAK, MOLLASE DAN EM4 TERHADAP PENURUNAN VOLUME SAMPAH ORGANIK DAN SAMPAH CAMPURAN - Ulfa . Nurullita (Universitas Muhammadiyah Semarang, 2003)
ABSTRACT Background: with field competition to throw waste away, motivates the need to treat the waste accurately. One of the treatments is to change waste into compos By composing, waste volume will decrease. If this thing can be applied in the Final waste Disposal so the field will be able to accommodate more waste. As a result of it, the effective term of final waste spot field can be prolonged. Naturally, waste can decay be decomposing but it takes a relatively long time. Furthermore, it takes treatment to speed up composing process. Object: the purpose of this research is to know waste Volume decrease of composing process with addition of various inoculan, such as bran, cow feaces, mollase and EM4 (Effective Microorganism 4) That contain a lot of micro organism and water that will help the leaching process. Method: type of this research is explanatory research with quasi experiment method, the design is pre-post test Control group design. There are 5 treatments, 3 replications and one control group. Results: Test result with one way anova indicate that there is a difference in organic waste volume decrease with addition of various inoculan and control. The difference of the biggest volume disease is on first treatment (63,7%), that is the addition of cow faeces, bran, mollase, EM4 and waster. This variety can work maximally. in control, the volume decrease is 51, 7%. One way Anova test towards organic-an organic waste indicate that there is no difference of waste volume decrease in many various inoculan and control. The difference of the biggest volume decrease is on fifth treatment (69%r), in control the volume decrease is 53%. This indicates that inoculan can not work within anorganic materials. Conclusion: The first treatment decreases the biggest volume. This variety can work maximally, Cow faeces and water will help the leachating process, especially for carbon material. Mollase and bran are food substance and source of energy for waste decomposer microorganisms, EM4 contain microorganisms that function as decomposers. But on organic-an organic waste inoculan can not work within an organic materials. Key words: Compos, cow faeces, mollase, Effective Microorganism 4.